2009
DOI: 10.1038/icb.2009.12
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic stromal cell implantation in brain tissue leads to robust microglial activation

Abstract: Although adult and embryonic stem cell-based therapy for central nervous system (CNS) injury is being developed worldwide, less attention is given to the immunological aspects of allogeneic cell implantation in the CNS. The latter is of major importance because, from a practical point of view, future stem cell-based therapy for CNS injury will likely be performed using well-characterised allogeneic stem cell populations. In this study, we aimed to further describe the immunological mechanism leading to rejecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 27 publications
4
40
1
Order By: Relevance
“…4F). This feature of glial reactivity (both microglia and astroglia) was seen as a sign of rejection of mesenchymal allografts, even in the absence of T-lymphocyte involvement (11,55). Given that we used syngeneic ENSPCs, and no T-cells (CD3 + cells) were seen (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4F). This feature of glial reactivity (both microglia and astroglia) was seen as a sign of rejection of mesenchymal allografts, even in the absence of T-lymphocyte involvement (11,55). Given that we used syngeneic ENSPCs, and no T-cells (CD3 + cells) were seen (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, assuming that labeling indicates that the cells, or their progeny, were grafted, survival was lower for ENSPCs than BNSPCs. Death of transplanted cells is a major hindrance for cell therapy (31), because of the small number of remaining cells to be incorporated, because of the local reaction caused by dying cells (55), and because of the structural changes incurred (48). Long-term studies have revealed a low yield of grafted cells over time (2,45).…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of allogeneic cell implants implies the need for immune suppression (e.g., towards inflammatory lesions (7,26,39). Although several studies reported on a beneficial effect of IV admincyclosporine A, CsA) in order to avoid acute or chronic rejection of cellular transplant in the CNS, as previously istered autologous NSCs on the clinical course of EAE (37,56), recent reports indicate that most-if not all-IV demonstrated by us (8,47,52) and others (9,28). Therefore, in the second therapeutically oriented part of this administered cells do not enter the CNS, but exert their therapeutic effect via immunomodulatory mechanisms study, we focus on the regenerative potential of IV administered allogeneic NSCs on EAE disease progression throughout the peripheral immune system (6,15,38).…”
Section: Introductionmentioning
confidence: 99%
“…All surgical interventions were performed under sterImmunofluorescence Microscopy ile conditions as previously described (8,52). Briefly, mice were anesthetized by an IP injection of a ketamine Immunofluorescence staining of NSC cultures, differentiated NSC cultures, BMSC cultures, and primary as-(80 mg/kg) + xylazine (16 mg/kg) mixture and placed in a mouse stereotactic frame.…”
Section: Dendritic Cell Cultures In Vitro Differentiation Of Nsc Cultmentioning
confidence: 99%
See 1 more Smart Citation